2019
DOI: 10.1111/1759-7714.12983
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous cone beam computed tomography‐guided bronchoscopic marking and video‐assisted thoracoscopic wedge resection in a hybrid operating room

Abstract: The increasing need for pulmonary resection by video‐assisted thoracoscopic surgery (VATS) has presented a greater opportunity to detect small‐sized pulmonary nodules by computed tomography (CT). In cases where it is difficult to identify tumor localization intraoperatively, it is necessary to place the VATS marker near the pulmonary nodules before surgery. Conventional percutaneous or bronchoscopic VATS marker placement under local anesthesia is accompanied by patient pain. We clinically applied a new techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…We performed wedge resection for benign SPN and lobectomy or segmental lung resection and lymph node dissection for malignant SPN, except for three patients who were converted to open surgery intraoperatively due to pleural atresia. This shows that both benign and malignant SPN can be diagnosed and effectively treated with VATS [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…We performed wedge resection for benign SPN and lobectomy or segmental lung resection and lymph node dissection for malignant SPN, except for three patients who were converted to open surgery intraoperatively due to pleural atresia. This shows that both benign and malignant SPN can be diagnosed and effectively treated with VATS [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported the usefulness of bronchoscopic marking. 21,22 Unlike percutaneous VATS marking, bronchoscopic marking does not damage the visceral pleura. Although bronchoscopic marking was not used in this study, the procedure is significantly superior to CT-guided percutaneous marking because of the lower incidence of iatrogenic pneumothorax.…”
Section: Discussionmentioning
confidence: 99%
“…It is advisable to prepare for thoracic drainage when placing a percutaneous VATS marker. Recent studies have reported the usefulness of bronchoscopic marking 21, 22 . Unlike percutaneous VATS marking, bronchoscopic marking does not damage the visceral pleura.…”
Section: Discussionmentioning
confidence: 99%
“…There is an emerging body of research into developing and evaluating localization techniques that can help targeted resection of small lung nodules 9‐12 . These techniques are combined with surgery and include intraoperative adjuncts (ultrasound, fluoroscopy); markers placed preoperatively or intraoperatively, such as hookwires, fiducials, microcoils, or radioactive seeds; dyes (methylene blue and indocyanine green [ICG]); and molecular targets (flourophores) 13‐24 .…”
Section: Introductionmentioning
confidence: 99%